2003
DOI: 10.1016/j.bbadis.2003.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of brain energy metabolism by the α-keto acids accumulating in maple syrup urine disease

Abstract: Neurological dysfunction is a common finding in patients with maple syrup urine disease (MSUD). However, the mechanisms underlying the neuropathology of brain damage in this disorder are poorly known. In the present study, we investigated the effect of the in vitro effect of the branched chain alpha-keto acids (BCKA) accumulating in MSUD on some parameters of energy metabolism in cerebral cortex of rats. [14CO(2)] production from [14C] acetate, glucose uptake and lactate release from glucose were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 38 publications
3
50
0
1
Order By: Relevance
“…Proposed mechanisms of neurotoxicity include energy deprivation and osmotic dysregulation (Howell and Lee 1963;Land et al 1976;Danner and Elsas 1989;Yudkoff et al 1994;Zielke et al 2002;Pilla et al 2003;Sgaravatti et al 2003;Ribeiro et al 2008) and alterations in the concentrations of the neurotransmitters glutamate, aspartate, and aminobutyric in the brain (Dodd et al 1992;Prensky and Moser 1967;Tavares et al 2000;Yudkoff et al 1994;Hutson et al 2001). The brain injury in this disorder may also be related to a reduction of brain uptake of essential amino acids (Araújo et al 2001;Wajner and Vargas 1999;Wajner et al 2000), apoptosis of neural cells (Jouvet et al 2000), oxidative stress (Bridi et al 2003(Bridi et al , 2005Fontella et al 2002;Barschak et al 2006;Mescka et al 2011), increased acetylcholinesterase activity in the brain (Scaini et al 2012), and alterations of neurotrophin levels (Scaini et al 2013a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanisms of neurotoxicity include energy deprivation and osmotic dysregulation (Howell and Lee 1963;Land et al 1976;Danner and Elsas 1989;Yudkoff et al 1994;Zielke et al 2002;Pilla et al 2003;Sgaravatti et al 2003;Ribeiro et al 2008) and alterations in the concentrations of the neurotransmitters glutamate, aspartate, and aminobutyric in the brain (Dodd et al 1992;Prensky and Moser 1967;Tavares et al 2000;Yudkoff et al 1994;Hutson et al 2001). The brain injury in this disorder may also be related to a reduction of brain uptake of essential amino acids (Araújo et al 2001;Wajner and Vargas 1999;Wajner et al 2000), apoptosis of neural cells (Jouvet et al 2000), oxidative stress (Bridi et al 2003(Bridi et al , 2005Fontella et al 2002;Barschak et al 2006;Mescka et al 2011), increased acetylcholinesterase activity in the brain (Scaini et al 2012), and alterations of neurotrophin levels (Scaini et al 2013a, b).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the latter, mouse model experiments have shown lower CSF levels of glutamate, dopamine, and GABA, as well as lower plasma levels of tryptophan, the precursor to serotonin (Zinnanti et al 2009). The BCKAs appear to exert effects, at least partially through disruption of pyruvate metabolism (Patel et al 1973) and respiratory chain function (Sgaravatti et al 2003). Nevertheless, the exact mechanism by which edema is generated remains unclear, thus designing and evaluating an effective initial management approach for a presymptomatic newborn infant with a positive newborn screen for MSUD is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that elevated !-ketoisocaproate might inhibit the pyruvate dehydrogenase complex causing the neuropathy (Kleopa et al 2001), and acute neuropathy is well recognized in pyruvate dehydrogenase deficiency (Debray et al 2006). Pyruvate has also been shown to inhibit BCAA oxidation in muscle (Buse et al 1972) and BCKA and BCAA have been shown to inhibit mitochondrial respiratory chain activity and ketoisocaproate to strongly inhibit pyruvate dehydrogenase activity in the brain of young rats (Ribeiro et al 2008;Sgaravatti et al 2003). Although blood thiamine levels were normal at the onset of symptoms and the patient was on thiamine supplementation, it is possible that thiamine requirements for the BCKD and pyruvate dehydrogenase complexes increase during decompen-…”
Section: Discussionmentioning
confidence: 99%